The raising of the professional orientation of physical training of future officers-communicators - Boroznyuk O.V (Kharkov National Pedagogical University, 2012)
The analysis of the characteristics of military and professional activity of officers-communicators and the requirements of this military expertise to the development of the body of cadets is performed. It is disclosed a question of a low professional orientation of physical training of cadets of higher military educational institutions and the necessity of its solving. The content of special physical training of future officers of signal is defined and practical recommendations to enhance the professional orientation of physical education students in related disciplines are proposed.